Legal Advertising and Warranty Liability: “Let the Lawyer Beware” - Marc I. Steinberg; Gerald E. Rosen (Washington University Law Quarterly, 1978)
This article will examine the realistic possibility of expanded lawyer liability by juxtaposing upon the clearly commercial flavor of legal advertising, the growing trend expanding warranty application under Article 2 of the Uniform Commercial Code by use of analogy.
Keywords: Advertising; Attorneys; Warranty